Diatomeae Paleogen trong lỗ khoan 81 và 104 ở miền võng Hà Nội và ý nghĩa của chúng - Nga, Đặng Đức; Cúc, Nguyễn Thị Thu (Vietnam Journal of Earth Sciences, 2004)
Paleogene Diatoms into borehole 81 and 104 in Hanoi depression